2017
DOI: 10.1016/j.jenvrad.2017.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Radiocesium in migratory aquatic game birds using contaminated U.S. Department of Energy reactor-cooling reservoirs: A long-term perspective

Abstract: Low-level releases of radiocesium into former nuclear reactor cooling-reservoirs on the U.S. Department of Energy's Savannah River Site (SRS) in South Carolina, USA, dating primarily to the late 1950s and early 1960s, have allowed examination of long-term contaminant attenuation in biota occupying these habitats. Periodic collections of migratory game birds since the 1970s have documented Cs (radiocesium) activity concentrations in birds of SRS reservoirs, including mainly Par Pond and Pond B. In this study, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…These differences between coot and diving duck 137 Cs levels have been attributed to species differences in diet (Brisbin et al ). However, species differences in residence time using contaminated sites, which is not well understood at this point, has the potential to explain substantial variation (Kennamer et al ); future research in this area is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences between coot and diving duck 137 Cs levels have been attributed to species differences in diet (Brisbin et al ). However, species differences in residence time using contaminated sites, which is not well understood at this point, has the potential to explain substantial variation (Kennamer et al ); future research in this area is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Pond A and R‐Canal also received 137 Cs‐contaminated effluent. Past work has quantified levels of 137 Cs in SRS cooling reservoir sediments (Whicker et al ), and related levels to those found in a variety of animals, including migratory game birds that can disperse contaminants extensive distances outside SRS boundaries (Brisbin et al , Kennamer et al ).…”
Section: Study Areamentioning
confidence: 99%
“…However, the levels of Hg found in blood never exceeded 0.2 mg/kg (wet wt, calculated from dry to wet ratios in Newman et al, 2011), placing them below background levels in a low-risk category for adverse health effects (Ackerman et al, 2016). Similarly, whole-body 137 Cs activity in our mallards from Fourmile did not exceed whole-body equivalent standards set by the EEC for human consumption (0.324 Bq/g, fresh mass; EEC, 1986) nor did their muscle tissues (0.600 Bq/g, fresh mass) using calculations for tissue moisture conversions from Kennamer et al (2017). While these Hg concentrations and 137 Cs activity found in Fourmile mallards are considered lower risk at the time of our study, there may be seasonal variation in bioavailability not reflected in the present study.…”
Section: Discussionmentioning
confidence: 62%
“…Our results were also similar to prior studies which found higher concentrations of 137 Cs in Pond B biota compared with Par Pond and elsewhere on the Savannah River Site (Kennamer et al, 1993; Oldenkamp et al, 2017; Paller et al, 1999). Prior studies of biota inhabiting Savannah River Site reservoirs have also shown longer ecological half‐lives of 137 Cs in sunfish (Paller et al, 1999), largemouth bass (Paller et al, 1999), and American coots (Kennamer et al, 2017) inhabiting Pond B compared with Par Pond. More recently, Fulghum et al (2019) found higher concentrations of 137 Cs in fish from Pond B compared with other components of the Par Pond system.…”
Section: Discussionmentioning
confidence: 94%